Enzymatic and histopathological changes in rat liver exposed to prenatal radiofrequency electromagnetic field: 3 generations - Fazile CANTURK TAN; Süleyman DAŞDAĞ; Gözde Özge KORKMAZ; Betül YALÇIN; Arzu Hanım YAY; Osman Çağrı İLHAN; Muhammet Ali GENÇASLAN; Burak TAN (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of our study is to investigate the enzymatic and histopathological effects of prenatal exposure to continuous 2450 MHz radiofrequency-electromagnetic field (RF-EMF) in rat liver. Material and Methods: In study we used 12 Wistar Albino adult female rats and 4 Wistar Albino adult male rats. They were divided into four groups of 1 male and 3 female rats. Control group was not exposed to EMF. The 1st group was exposed male rats but not exposed female rats by continuous 2450 MHz EMF. The 2nd group was exposed both male rats and female rats by continuous 2450 MHz EMF. The 3rd group was not exposed male rats and were exposed female rats by continuous 2450 MHz EMF. Before EMF application, all groups were placed into Faraday Cages. Exposure RF was 12 hours from 08:00 to 20:00 hours every day for 30 days. At the end of 30 days all groups were fertilized. On the 18th day of the gestational period, one pregnant rat was sacrificed under general anesthesia and fetuses were taken. The livers of the fetuses were taken into 10% formaldehyde for histopathological evaluation. The other two rats completed the normal delivery process. When the rats were two months old, 3 female and 1 male rats from each group were separated for other generations. The remaining rats were sacrificed under general anesthesia. The level of malondialdehyde (MDA) in the liver of the rats was enclosed in a -800C refrigerator for catalase (CAT) and superoxide dismutase (SOD) activity and 10% formaldehyde for histopathological evaluation. Sections were stained with hematoxylin-eosin (H&E). The same experiment protocols were continued and the study was completed in 3 generations. Results: There was an increase in the first and third generation MDA levels and a decrease in SOD and CAT activities in the exposure groups compared to the control. Liver histology was normal in the control group. When the liver sections of the first group were compared with the control group, hepatocyte degeneration was observed with hemorrhage and some cytoplasmic vacuolizations. There was hemorrhage, hepatocyte degeneration in the parenchymal areas and some necrotic areas in the liver tissues belonging to the second group. When the liver tissue belonging to the third group was examined, it was similar to the first group but less than the second group, hemorrhage, hepatocyte degeneration and necrosis were observed. Conclusion: When the findings are compared, our data shows that continuous RF-EMF causes oxidative stress and histopathological changes in the rat liver. Acknowledgments: This work was supported by the Erciyes University-The Scientific Research Projects of Turkey (ERUBAP); Project number: TYL-2017-7110.